The Effect of Temperature Manipulation on Skeletal Muscle Function and Thermal Stress Responses in Young Males (Baltic Journal of Sport and Health Sciences, 2025)
Background and objectives: Temperature manipulation, through heating and cooling strategies such as hot or cold water immersion (HWI, CWI) or exertional heating, alters body temperature and can influence muscle function, metabolic activity, recovery, and thermal stress responses (Cramer et al., 2022; Rodrigues et al., 2022; Versey et al., 2013). These interventions can elevate or reduce core and muscle temperature (Tmu), leading to distinct effects on muscle contractility, fatigue, recovery, and endocrine responses (Bergh & Ekblom, 1979; Cheng et al., 2017; Morton et al., 2007; Mündel et al., 2006). Prolactin is often used as an indirect marker of central fatigue and heat-related stress (Mündel et al., 2006), however, it is unclear whether endocrine responses differ when core temperature increases are closely matched but skin temperature varies between active (exercise-induced, Exer-H) and passive (exogenous, Exo-H) heating. The mechanisms underlying neuromuscular and thermal stress responses remain unclear, particularly regarding the influence of exposure duration and differences between active and passive heating modalities. The general aim of the dissertation was to determine the effects of heating and cooling of varying durations on skeletal muscle function and thermal stress responses in recreationally active young males.Methods: Four studies were conducted. In Study I, a randomised crossover design was used, in which participants completed both active (exercise-induced) heating (cycling at 60% V̇O2max until rectal temperature (Trec) reached 39°C) and passive (exogenous) heating (lower-body immersion in hot water until Trec reached 39°C). Study II comprised four randomised cross-over experimental trials across two phases: a single exposure phase (SP) for 45 min and an intermittent/prolonged exposure phase (IPP) for 300 min, each including control sitting (CON) and hot water immersion (HWI at 44–45°C up to the waist) performed in random order and separated by at least one week, with muscle force and contractile properties assessed during the experiments. Study III followed the same design as Study II, but used cold water immersion (CWI at 10°C up to the waist) instead of HWI. Study IV combined the protocols of Studies II and III, with participants completing six experimental trials: acute (CON, HWI, CWI) and intermittent/prolonged (CON, HWI, CWI), along with additional assessments of muscle force recovery.• Study I (subjects: young healthy males (n = 14, age: 5 ± 4.1 years): measurements were taken at 0.5°C increase in Trec up to 39°C and during the subsequent decrease down to 37.5°C, including muscle temperature, skin temperature (Tsk), rectal temperature, blood samples for prolactin concentration assessment, and thermal perceptions.• Studies II and III (subjects: recreationally active males (n = 12, age: 27.2 ± 6.6 years). Single (SP) and intermittent/prolonged (IPP) hot water (HWI) or cold water (CWI) immersion. During intermittent/prolonged CWI phase, two additional 15 min immersions were added at 165 min and 255 min, while during intermittent/prolonged HWI, eight additional bouts of HWI were added after 75, 105, 135, 165, 195, 225, 255, and 285 min. Participants underwent measurements of body composition, cardiovascular parameters (heart rate, blood pressure), rectal (Trec) and muscle (Tmu) temperature, and neuromuscular function (P20, P100, TT, maximal voluntary isometric contraction (MVIC), dynamic knee exercises) at baseline and multiple time points during single and intermittent/prolonged immersion. Both phases concluded with a fatiguing protocol of 100 electrical stimulation trains to the knee extensors.• Study IV (subjects: recreationally active males (n = 10, age: 1 ± 6.8 years). The participants for Study IV are a subset from studies II and III. Assessed the effects of acute and prolonged temperature exposure on muscle recovery, including neuromuscular testing 3 min after fatiguing exercise.Results:In Study I, the Δ changes in prolactin concentration were larger in Exo-H compared to Exer-H during both the heating phase (P = 0.011) and post-heating (P = 0.009) phases. The increase in Tsk Calf and Tsk Thigh was larger in Exo-H compared to Exer-H during the heating phase (P